The concept of nonviolence and animal protection in Thēravāda Buddhist ethics. - โลกะนัง, พระสมุห์อดิเรก อาทิจฺจพโล (Journal of Buddhist Studies Chulalongkorn University, 2019)
This article discusses the concept of nonviolence or Ahimsa with regard to animal protection in Thēravāda Buddhist ethics. It attempts to respond to Western animal rights groups that have criticized Thēravāda Buddhism for being speciesist, treating animals as mere properties, and considering animals as having lower ethical status than humans. According to these views, Thēravāda Buddhism makes no mention of intrinsic values of other lifeforms, and is therefore human-centric. Speciesism is the view that tends to prioritize the interests of members of one’s own species as opposed to those of others. However, this article wishes to defend Thēravāda Buddhism by using 3 main arguments: 1) Thēravāda Buddhist ethics does not contain any speciesist view and in no way supports the killing or using of animals as means to further ends; 2) Thēravāda Buddhism contains teachings on the intrinsic values of all lifeforms; and 3) Thēravāda Buddhism judges the actions and both humans and animals equally and extends the principle of nonviolence (Ahimsa) to animals.